2016
DOI: 10.1055/s-0042-110792
|View full text |Cite
|
Sign up to set email alerts
|

Das praktische Vorgehen beim postoperativen und posttraumatischen Lymphödem

Abstract: Swelling of the extremities is frequently observed after traumatic lesions and poses differential diagnostic challenges. Causes include seromas, haematomas and thromboses, as well as lymphostatic oedemas, which may become chronic if left untreated. These are characterized by a high percentage of protein and, over the long term, they can lead to considerable impairment and complications such as recurrent erysipelas as a result of fibrotic tissue rearrangement. Usually a clinical diagnosis is made, which presupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, prompt treatment of pain, widely-regarded as the fifth vital sign, is beneficial for reducing suffering, readmissions and emergency department visits after hospital discharge [ 36 ]. Although many studies have reported on how to eliminate chronic post-traumatic lymphedema [ [37] , [38] , [39] ], the effect of lymphatic drainage on acute post-traumatic hematoma and pain is not clear. With the treatment of anti-PDPN neutralizing antibody, we determined that improving lymphatic drainage reduces acute post-traumatic edema and pain, suggesting that defects in lymphatic drainage plays a key role in the early complications of traumatic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prompt treatment of pain, widely-regarded as the fifth vital sign, is beneficial for reducing suffering, readmissions and emergency department visits after hospital discharge [ 36 ]. Although many studies have reported on how to eliminate chronic post-traumatic lymphedema [ [37] , [38] , [39] ], the effect of lymphatic drainage on acute post-traumatic hematoma and pain is not clear. With the treatment of anti-PDPN neutralizing antibody, we determined that improving lymphatic drainage reduces acute post-traumatic edema and pain, suggesting that defects in lymphatic drainage plays a key role in the early complications of traumatic fracture.…”
Section: Discussionmentioning
confidence: 99%